2020
DOI: 10.2106/jbjs.20.00617
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Proximal Femoral Fragility Fractures in Patients with COVID-19 During the SARS-CoV-2 Outbreak in Northern Italy

Abstract: The purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts. Identifying information. The work under considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(161 citation statements)
references
References 11 publications
6
149
2
4
Order By: Relevance
“…Nevertheless, the Northern Italian experience reported by Catellani et al showed that prompt surgical treatment for proximal femoral fractures resulted in improvement of respiratory parameters in symptomatic COVID-19 patients. 13 Additionally, the preliminary results of the Spanish HIP-COVID multi-centre study demonstrated that at 14-days post-admission, the mortality rate among hip fracture patients treated conservatively was 67%, compared to 4% for patients who were treated surgically. 14 These studies add significant strength to the evidence that supports prompt surgical treatment in hip fracture patients despite stretched medical resources during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Northern Italian experience reported by Catellani et al showed that prompt surgical treatment for proximal femoral fractures resulted in improvement of respiratory parameters in symptomatic COVID-19 patients. 13 Additionally, the preliminary results of the Spanish HIP-COVID multi-centre study demonstrated that at 14-days post-admission, the mortality rate among hip fracture patients treated conservatively was 67%, compared to 4% for patients who were treated surgically. 14 These studies add significant strength to the evidence that supports prompt surgical treatment in hip fracture patients despite stretched medical resources during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the World Health Organisation has reported that of those who have tested positive worldwide, 6.9% have died [20]. In hospital, mortality rates have varied in the literature from 15 to 28.5% [13][14][15][16][21][22][23]. A recent UK study of 16,749 patients admitted to hospital with COVID-19 reports a mortality rate of 31% for patients with a wardbased level of care [10].…”
Section: Discussionmentioning
confidence: 99%
“…The total number of surgical procedures reported in the included studies was 1370, including gastrointestinal/abdominal (n¼393), 18,20,25,33,40 orthopaedic (n¼352), 17,18,20,33,40,41 obstetric/gynaecologic (n¼166), 16,19,21e23,26,28e31,33e41 cardiothoracic/vascular (n¼146), 20,24,27,33,40 hepatobiliary (n¼62), 33 neurosurgical (n¼47), 20,33,40 head and neck (n¼40), 33 urologic (n¼37), 33 other surgeries (n¼63), 33,40 and missing details (n¼64). 32,33 The schedule of surgeries, where reported, were classed as elective (n¼316), and urgent or emergency (n¼949).…”
Section: Covid-19 Statusmentioning
confidence: 99%
“…27 Postoperative respiratory support was described in 10 studies, 17,18,20,23,24,26,27,31,33,37 but as with ICU use it was not clear in some papers whether this would have occurred anyway. Postoperative use of analgesia was only reported in three studies, 17,28,37 with only one reporting any formal pain assessment. 19 Reporting of outcomes in neonates was more consistent, with 16 studies (out of 19 studies involving obstetric surgeries) reporting COVID-19 status 16,19,21e23,26,28e31,34e39 and 12 of those studies reporting only negative test results, mainly for RTePCR.…”
Section: Patient Outcomesmentioning
confidence: 99%